The Effect of Communal Cognitive-Behavioral Therapy Over Addiction Potential and Addiction Tendency of Students Suffering from Social Phobia - Lak, Zahra; Sedaghat, Masoumeh; Ahmadvand, Zahra (Richtmann Publishing, 2012)
The aim and background: This present research has been done in order to review the effectiveness of communal behaviouralcognitivetherapy over addiction potential and tendency of Shahed university students suffering from social phobia. The method ofresearch: This research is a study over clinical trial. The sample of research included 30 students of Shahed University who had got thehighest score according to social phobia test on SPIN and suffering from social phobia. Before entering into therapy, these studentsresponded to both addiction potential questionnaire (APS) and addiction acknowledgment questionnaire (AAS). After beinghomogenized, the samples divided into two groups of control and experimental. The experimental group placed under train ofbehavioural-cognitive therapy over 20 sessions and the control group did not place under any training program. The data collectioninstrument was self reporting which was analysed, using the descriptive statistics, the correlation coefficient, the covariance analysis andSPSS 19 software. Findings: There has been a significant different between addiction potential and addiction tendency while enteringinto research, after therapy and 6 weeks later, but from this view, no significant difference was observed in control group. It means thatbehavioural-cognitive therapy has effect on reduction of addiction potential and tendency.